Structural Violence in the Jokes about the Indigenous Mangyans of Oriental Mindoro, Philippines - Mahaguay, Jerwin M. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper focuses on the jokes directed towards the indigenous people (IPs), particularly the Mangyans of Oriental Mindoro, Philippines. It aims to show that these jokes contain violent messages directed to oppress the Mangyans as a race structurally. Whether conscious or not, its speakers are engaged in transmitting violence that demeans the Mangyans. Iris Marion Young’s theory about structural violence is the theoretical guide for this study.